Differential Associations Between Parents' Versus Children's Perceptions of Parental Socialization Goals and Chinese Adolescent Depressive Symptoms - Zhou, Zexi; Li, Mengtong; Wu, Jiawen; Li, Xiaoru (Frontiers in Psychology, 2021)
Although prior studies have demonstrated the associations between parental socialization goals and parenting practices, as well as parenting practices and adolescent depressive symptoms respectively, research examining the comprehensive developmental pathways among these constructs (i.e., the path from parental socialization goals to parenting practices to adolescent depressive symptoms) is scarce, especially in the Chinese context. Grounded in the integrative model of parenting, this study investigated the associations between parental socialization goals and adolescent depressive symptoms by examining the indirect pathways through parents’ autonomy support and psychological control as well as the moderating effect of educational stage. In Study 1, 345 Chinese adolescents and their primary caregivers completed a measure on parental socialization goals. Adolescents also reported on their depressive symptoms. Results showed that children who reported more self-development parental goals showed fewer depressive symptoms. However, parents’ reports of goals or child-parent perceptual discrepancies were not related to children’s depressive symptoms. Drawing on this finding, 424 middle school and 301 high school Chinese adolescents completed measures regarding parental socialization goals, autonomy support, psychological control, and their own depressive symptoms in Study 2. Results showed that parental autonomy support linked the associations of self-development and achievement-oriented parental goals and children’s depressive symptoms among middle school students, whereas parental psychological control linked such associations among high school students. Our findings provide a more holistic view on how parents’ socialization goals are related to children’s depressive symptoms via their parenting practices. We also discussed the practical implications for the clinical work regarding adolescent depressive symptoms.